ANALYSIS OF ANNUAL SPT REPORTING IN IMPROVING INDIVIDUAL TAXPAYER COMPLIANCE WITH KPP PRATAMA MEDAN BELAWAN - Siraj, Rifqi (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this research is to determine Annual SPT Reporting in Increasing Individual Taxpayer Compliance at KPP Pratama Medan Belawan. The method used in this research is descriptive. The type of data used is primary data, namely the results of interviews from the company regarding income recognition and secondary data in the form of personal tax data at KPP Pratama Medan Belawan. The analysis carried out in this research is a descriptive technique. Based on the research results, it can be concluded that the reason why there are still individual taxpayers who do not submit their Individual Annual Tax Returns. The reason is that individual income tax revenues have not reached the target. There are registered personal taxpayers who are no longer operating but have not submitted an application as non-effective taxpayers at KPP Pratama Medan Belawan